Training in Making Tempeh in Character Molds to Increase Elementary School Students' Interest in Consuming Tempeh - Ihwana As’ad; Martriwati; Satriya Nugraha; Ariyani Muljo; Ika Purnama Sari; Hanrezi Dhania; Yuliana Mose; Zunan Setiawan; Jasiah; Nuris Kushayati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Tempeh, a traditional Indonesian fermented soybean product, is highly nutritious but under-consumed by children due to its bland appearance and unfamiliar texture. This community service program aimed to enhance elementary school students’ interest in consuming tempeh through a participatory training that introduced character molds into the tempeh-making process. Conducted with 20 students aged 9–11 years, the intervention employed a pretest-posttest design to assess changes in tempeh preferences, knowledge, and willingness to consume and prepare tempeh. Results indicated significant improvements across all indicators: students’ liking of tempeh increased from 35% to 85%, their perception of its visual appeal rose from 25% to 90%, and willingness to try character-shaped tempeh reached 95%. The program not only improved students’ understanding of tempeh’s nutritional benefits but also engaged them in creative, hands-on food preparation that enhanced motivation and enjoyment. The findings support the use of experiential learning and visual food design in child nutrition education. This initiative effectively combined cultural food preservation with innovative teaching strategies. It demonstrates that integrating fun and creativity into traditional food education can promote healthier eating habits and strengthen local food identity among young learners. Future programs should consider scaling up and incorporating family and school-level involvement to achieve a broader and more sustainable impact.